Participation in Tourism Village Development In Turgak Village Subdistrict Belalau West Lampung - Asmaria Asmaria; Rini Setiawati; Arnila Rosimah Arnila Rosimah (STMIK Dharma Wacana, 2023)
Lack of participant development tourism in Turgak Village, because That study This aim For study participation public in development of Turgak Village, with focus make village the as destination tour. Study This use design qualitative with method interviews and observations , meanwhile data analysis using technique interactive. Research result showing that participation public in development of Turgak Village increasingly low. Next, factors the barrier including deficiencies understanding about potential of tourist villages, reluctance a number of inhabitant For participation, and the lack of it innovation in development object tour. Although has There is effort self-help and mutual cooperation development, still required follow carry on from government local For increase more participation and management Good. Therefore that's important participation public in development of Tourism Villages recognized as key success.